Optical properties of cross-linked chitosan thin film for copper ion detection using surface plasmonresonance technique - Wing Fen, Yap; Mat Yunus, W. Mahmood; Yusof, Nor Azah (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
The cross-linked chitosan is synthesized by homogeneous reaction of medium molecular weight chitosan in aqueous acetic acid solution with glutaraldehyde as cross-linking agent. Using surface plasmon resonance technique, the optical properties of cross-linked chitosan thin film before and after contacting with different concentrations of copper ion in a range of 0 to 100 ppm had been obtained by fitting. The imaginary part of refractive index increased while the thickness of the film decreased as copper ion concentration increased from 0 (deionised water) to 100 ppm. The resonance angle shifted to lower value as the copper ion concentration increased. By introducing the cross-linked chitosan film, copper ion detection can be obtained for concentration as low as 0.5 ppm using surface plasmon resonance technique.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 999-1013
Keywords: optyka; cross-linked chitosan; copper ion; surface plasmon resonance